Penerapan strategi pembelajaran Cooperative Learning dalam meningkatkan keterampilan menulis: The Implementation of Cooperative Learning Strategies in Enhancing Students' Writing Skills - Abrori Sayfy Mardiani (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2026)
This research is based on the low ability of students in Arabic writing skills because of the limited use of active and cooperative learning strategies. The purpose of this research is to describe the implementation of the Cooperative Learning strategy in developing students’ writing skills at Ma’had Aly Lirboyo and Modern Darul Hikmah Islamic Boarding School Tawangsari. The subjects of this research were first-year students (S1) at Ma’had Aly Lirboyo and seventh-grade students (ninth MA) at Modern Darul Hikmah Islamic Boarding School Tawangsari. The participants were twenty students selected through purposive sampling based on their Arabic writing ability. This research used a qualitative descriptive method. The research instruments were observation, interviews, and documentation. Data were collected through observing learning activities, interviewing teachers and students, and analyzing students’ writing documents. The data analysis process included data reduction, data display, and drawing conclusions. The results showed that the Cooperative Learning strategy was able to improve students’ writing skills through group discussions, peer correction, and collaborative writing. Students became more active in arranging sentences, developing ideas, and correcting grammar mistakes together. The research concluded that the Cooperative Learning strategy is effective in teaching Arabic and developing students’ writing skills in an active, organized, and cooperative way.